Determinants of purchase behavioural intention on vitamin supplement among young adults in Malaysia - Siew, Jun Yaw; Teoh, Zhi Ming (2018)
The research study are developed to investigate the determinants of purchase behavioural intention of vitamin supplement among young adults in Malaysia. The main concern of this study will be around the identified factors includes brand image, customer satisfaction, trust, perceived risk and perceived value in influencing the young adults purchase behavioural intention towards vitamin supplement. There are seven hypotheses constructed in order to study and generate comprehensive results. The target respondents in the study are Malaysians who are within the age range of 18 to 40 years old. In addition, 200-sets of valid questionnaires were collected and being analysed by using Statistical Package for Social Science (SPSS) version-23. The researchers adopted Simple Linear Regression, Multiple Linear Regression and Causal Test for Mediation Analysis. Moreover, prior of the inferential analysis, the results of internal reliability test (Cronbach’s Alpha) indicated that the measurement scales were consistent and reliable in measuring the proposed constructs. According to results generated from Multiple Linear Regression and Simple Linear Regression, all the variables (brand image, customer satisfaction, perceived risk and perceived value) except for trust indicating a significant positive relationship. Apart from that, the mediating variable (perceived value) showed a partial mediation effect upon the relationship between brand image and purchase behavioural intention. Lastly, few limitations that hinder the research to be conducted effectively were identified and recommendations are presented to propose beneficial suggestions for further studies to be conducted.